Incorporation of fatty acids from fish oil and olive oil into colonic mucosal lipids and effects upon eicosanoid synthesis in inflammatory bowel disease. Issue 10 (October 1991) - Hillier, K; Jewell, R; Dorrell, L; Smith, C L
Abstract : The incorporation of the fatty acids in fish and olive oil into the colonic mucosa of patients with inflammatory bowel disease was examined during 12 weeks' dietary supplementation with the oils, and the influence on colonic mucosal prostaglandin and thromboxane generation was measured. With a dietary supplement of 18 g fish oil daily, concentrations of the major polyunsaturated fatty acids in fish oil, eicosapentaenoic acid and docosahexaenoic acid, were significantly raised in mucosal lipids. The first time these were measured, after three weeks' supplementation, the mean increases in eicosapentaenoic and docosahexaenoic acid were seven fold and 1.5 fold respectively, and these increases were maintained during the 12 week study. Arachidonic acid values fell throughout the study and this reduction was significant at 12 weeks. Mucosal prostaglandin E2 (PGE2), thromboxane B2, and 6-keto prostaglandin F1 alpha synthesis were suppressed, and this reached significance (p less than 0.05) at three and 12 weeks for PGE2 and at 12 weeks for thromboxane B2. The predominant fatty acid in olive oil is oleic acid. Supplementation with 18 g/day resulted in a significant increase in oleic acid in colonic mucosa at 12 weeks (p less than 0.05) and a fall in stearic acid and docosahexaenoic acid; there was no significant change in eicosanoid synthesis. It is concluded that colonic lipids and prostaglandin and thromboxane synthesis can be readily altered by dietary supplementation with fish oil. The extent of incorporation of the fatty acids present in oils is dependent upon the individual fatty acid.